Analisis Pengelolaan Zakat di Pondok Modern Daarul Ilmi Menurut Hukum Islam dan UU No. 23 Tahun 2011 tentang Pengelolaan Zakat - Rifa Ardi Gumelar; Siska Lis Sulistiani (UPT Publikasi Ilmiah Unisba, 2021)
Abstract. Islam regulates zakat and its management as well as the law, the law governing zakat management is contained in Law Number 23 of 2011 concerning zakat management, which in Article 38 states that zakat management may not be carried out by any person without the approval of the authorities. Daarul Ilmi Islamic Boarding School has been carrying out zakat management activities since 2010 until now, but Daarul Ilmi Islamic Boarding School does not yet have legality from the authorities to manage zakat. This study aims to find out how to manage zakat according to Islamic law and Law Number 23 of 2011 concerning zakat management, and to find out how to manage zakat in Darul Ilmi Islamic Boarding School according to Islamic law and Law No. 23 of 2011 on zakat management. The method used in this study is juridical normative. In Islamic law, zakat management can be carried out by anyone without certain legalities, only to be appointed by a leader, but in Law Number 23 of 2011 Article 38 there must be legality or permission from the authorities, therefore Darul Islamic boarding school is appropriate or appropriate. In line with Islamic law regarding the management of zakat, but not according to Law Number 23 of 2011. Abstrak. Agama Islam mengatur mengenai zakat beserta pengelolaannya begitupun dengan UU. UU yang mengatur mengenai pengelolaan zakat terdapat pada UU No. 23 Tahun 2011 tentang pengelolaan zakat, yang mana pada Pasal 38 menyebutkan bahwa pengelolaan zakat tidak boleh dilakukan oleh sembarangan orang tanpa persetujuan dari pihak yang berwajib. Pondok Pesatren Daarul Ilmi telah melakukan kegiatan pengelolaan zakat semenjak Tahun 2010 hingga saat ini, akan tetapi Pondok Pesantren Daarul Ilmi belum mempunyai legalitas dari pihak yang berwajib untuk mengelola zakat. Penelitian ini bertujuan untuk mengetahui bagaimana pengelolaan zakat menurut hukum Islam dan UU No. 23 Tahun 2011 tentang pengelolaan zakat, serta mengetahui bagaimana pengelolaan zakat di Pondok Pesatren Darul Ilmi menurut hukum Islam dan UU No. 23 Tahun 2011 tentang pengelolaan zakat. Metode yang digunakan dalam penelitian ini adalah yuridis normatif. Didalam hukum Islam pengelolaan zakat dapat dilakukan oleh siapa saja tanpa ada legaliats tertentu hanya di tunjuk oleh seoarang pemimpin, akan tetapi didalam UU No. 23 Tahun 2011 Pasal 38 harus adanya legalitas atau izin dari pihak yang berwajib, maka dari itu pondok pesatren darul sudah sesuia atau sejalan dengan hukum Islam mengenai pengelolaan zakat, akan tetapi belum sesuai menurut UU No. 23 Tahun 2011.